Optimal selection of LQR parameter using AIS for LFC in a multi-area power system - Muhammad Abdillah; Herlambang Setiadi; Adelhard Beni Reihara; Karar Mahmoud; Imam Wahyudi Farid; Adi Soeprijanto (National Research and Innovation Agency, 2016)
This paper proposes a method to optimize the parameter of the linear quadratic regulator (LQR) using artificial immune system (AIS) via clonal selection. The parameters of LQR utilized in this paper are the weighting matrices Q and R. The optimal LQR control for load frequency control (LFC) is installed on each area as a decentralized control scheme. The aim of this control design is to improve the dynamic performance of LFC automatically when unexpected load change occurred on power system network. The change of load demands 0.01 p.u used as a disturbance is applied to LFC in Area 1. The proposed method guarantees the stability of the overall closed-loop system. The simulation result shows that the proposed method can reduce the overshoot of the system and compress the time response to steady-state which is better compared to trial error method (TEM) and without optimal LQR control.